THE EFFECTIVENESS OF KWL (KNOW-NOW-WANT TO KNOW-LEARNED) FOR THE TENTH GRADERS OF MA MU’ALLIMIN NW PANCOR IN THE SCHOOL YEAR 2014-2015 - Mashur (Scientium Management Review, 2022)
This study aimed at examining the effectiveness of KWL strategy for the tenth graders of MA Mu`allimin NW Pancor in the school year 2014-2015. The problems formulated in this study were (1) Is KWL strategy effective in teaching reading comprehension of descriptive texts for the tenth graders of MA Muallimin NW Pancor in the school year 2014-2015? and (2) How is the effectiveness of KWL strategy in teaching reading comprehension of descriptive texts for the tenth graders of MA Muallimin NW Pancor in the school year 2014-2015?. This research applied experimental methodology. The population was the tenth graders of MA Muallimin NW Pancor consisted of 7 classes. The present researcher took one class as the sample there were 30 students in X Bahasa1 as the experimental class. To collect the data, a pre- test and a post-test were given to the students for the tenth graders. For technique of analyzing data, the present researcher used SPSS 17 for windows. After submitting the data to paired samples t-test, the present researcher found that there was a significant difference in the mean scores between the pre-test and the post-test, t(df=32) =7.493 at p = 0.001, meaning that the null hypothesis was rejected and alternative hypothesis was accepted. KWL Strategy was significantly effective in teaching reading comprehension of descriptive texts for the tenth graders of MA Muallimin NW Pancor in the school year 2014- 2015